PRAKTIK BENTUK BANTEN PRAYASCITA DI KOTA DENPASAR - Ni Ketut Sukiani (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2017)
[Title: The form of Banten Prayascita at Denpasar City] In the implementation of Hindu traditional reigious ceremonies in Bali, they are many types and forms of bantens are used. This causes the people’s lack understanding of the correct form of the banten. Especially on Prayascita banten, where this banten has various forms. This study aims to deepen the knowledge of the forms of Prayascita banten used in the conduct of religious ceremonies by Hindu people, thus will let people know the right form of banten Prayascita. In this research, the data source obtained by doing literature review and interviews to interviewees who are experts in religion as well as experts in making the banten itself. This research uses qualitative research methods through a qualitative approach that spend more focuses on the integrity of a cultural phenomenon. Banten Prayascita is one of many kinds of banten which has a very important function and always used in every implementation of Hindu traditional religious ceremony. There are various forms of Prayascita banten used in Hindu ceremonies. The most common forms of Prayascita banten are banten Prayascita biasa, banten Prayascita sakti, and banten Prayascita luwih.